The Happy Victimizer Pattern in Adulthood: State of the Art and Contrasting Approaches: Introduction to the Special Issue - Gutzwiller-Helfenfinger, Eveline; Heinrichs, Karin (Frontline Learning Research, 2020)
no abstract